Dynamic Relationship Between Water Resources and New Urbanization Based on a Vector Autoregressive Model: A Case Study of Hebei Province, China - Li, Shule; Yan, Jingjing; Pei, Qiuming; Sha, Jinghua; Liu, Fei (Frontiers in Environmental Science, 2022)
Overly rapid urban expansion in the past has significantly changed water resources, resulting in an imbalance between water resources and the sustainable development of new urbanization. To facilitate the sustainable development and utilization of water resources and promote the high-quality development of new urbanization, this study constructs evaluation index systems for water resources and new urbanization. Taking Hebei Province, China, as an example, the long-term equilibrium relationship between water resources and new urbanization as well as the dynamics are empirically analyzed using a vector autoregressive model with a variable cointegration test, generalized impulse responses, and a decomposition prediction method using evaluation result data for the 2000-2019 period. The results indicate an upward trend for water resources and new urbanization in Hebei during the 2000-2019 period, reflecting gradual improvements in the overall situation for these two factors. There is indeed a supporting and inhibiting dynamic relationship between new urbanization and water resources as well as their components. Declining water resource support and serious water pollution have gradually become important factors limiting new urbanization in Hebei, and the constraining effects of the reduced water ecological carrying capacity and water disaster damage have gradually decreased. For future development, decision makers in Hebei should fully consider the positive role of new urbanization in promoting water resources and water environments, slow the rate of water resource consumption by strengthening water conservation measures and optimizing the water utilization structure, and enhance the stability of water environments by increasing investments in water pollution prevention.